Predicting 2‐year all‐cause mortality after contemporary PCI: Updating the logistic clinical SYNTAX score. Issue 7 (4th February 2021) - Chichareon, Ply; van Klaveren, David; Modolo, Rodrigo; Kogame, Norihiro; Takahashi, Kuniaki; Chang, Chun‐Chin; Tomaniak, Mariusz; Yuan, Jinqing; Xie, Lihua; Song, Ying; Qiao, Shubin; Yang, Yuejin; et al.
Abstract: Aims: We aimed to update the logistic clinical SYNTAX score to predict 2 year all‐cause mortality after contemporary percutaneous coronary intervention (PCI). Methods and results: We analyzed 15, 883 patients in the GLOBAL LEADERS study who underwent PCI. The logistic clinical SYNTAX model was updated after imputing missing values by refitting the original model (refitted original model) and fitting an extended new model (new model, with, selection based on the Akaike Information Criterion). External validation was performed in 10, 100 patients having PCI at Fu Wai hospital. Chronic obstructive pulmonary disease, prior stroke, current smoker, hemoglobin level, and white blood cell count were identified as additional independent predictors of 2 year all‐cause mortality and included into the new model. The c‐indexes of the original, refitted original and the new model in the derivation cohort were 0.74 (95% CI 0.72–0.76), 0.75 (95% CI 0.73–0.77), and 0.78 (95% CI 0.76–0.80), respectively. The c‐index of the new model was lower in the validation cohort than in the derivation cohort, but still showed improved discriminative ability of the newly developed model (0.72; 95% CI 0.67–0.77) compared to the refitted original model (0.69; 95% CI 0.64–0.74). The models overestimated the observed 2 year all‐cause mortality of 1.11% in the Chinese external validation cohort by 0.54 percentage points, indicating the need for calibration of the model to the Chinese patient population. Conclusions: The new model of the logistic clinical SYNTAX score better predicts 2 year all‐cause mortality after PCI than the original model. The new model could guide clinical decision making by risk stratifying patients undergoing PCI.